Proposal for a Network of Protective Teachers for LGBTIQ+ StudentsBased on Queer Pedagogy in the Town of San Antonio de Prado,Medellín - Betancur Ortiz, Victor Georlan (Emerging Trends in Education, 2026)
This research makes visible the conflicts and violence related to the diversity of gender identities in schools in the town of San Antonio de Prado, Medellín, from a queer pedagogy approach. Through a qualitative multiple case study design, the perceptions of (in)safety of LGBTIQ+ students and the attitudes and teaching practices towards this population were explored. The findings reveal a web of exclusions, resistances and possibilities for transformation in the school context. The students’ voices reveal multiple forms of violence and coping strategies deployed to inhabit the school. The analysis of teachers’ attitudes reveals tensions between openness and prejudices rooted in heteronormative imaginaries. There is evidence of peripheral pedagogical practices that relegate LGBTIQ+ identities to the margins of the curriculum, but also of initiatives by some teachers who assume an ethical responsibility for inclusion. These findings question the foundations that sustain exclusion in schools and invite us to imagine other ways of doing education from dissidence. Recommendations are put forward for future research, educational interventions and public policies that bet on a profound transformation towards therecognition and celebration of diversity